The cryptic Sebacinales: An obscure but ubiquitous group of root symbionts comes to light. (August 2016) - Bokati, Deepak; Craven, Kelly D.
Abstract: The ubiquitous fungal order Sebacinales has the greatest diversity of mycorrhizal-types and is the earliest lineage containing such symbionts to diverge within the Basidiomycota. Two members of the Sebacinales, Piriformospora indica and Sebacina vermifera, have received most of the attention because of their growth-enhancing effects on a variety of host plants. Despite their worldwide distribution, axenic cultures of sebacinoids are extremely rare, and most of the knowledge gained thus far has been inferred using environmental and root tissue DNA. The global distribution of these fungi suggests host-tracking to novel habitats, sharing hosts within a habitat, and a general lack of host specificity. Their propensity as both saprotrophs and plant growth-promoting symbionts makes them strong candidates to be deployed for ecosystem restoration, bioremediation, and sustainable low-input agricultural efforts.